Peranan Dinas Lingkungan Hidup dalam Mengendalikan Pencemaran Sungai di Kabupaten Jombang - Nara Rizky Ramadhan, Arianto; Tukiman, Tukiman (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This research aims to analyze the role od the Jombang Regency Environmental Service in controlling river pollution in order to rebuild environmental cleanliness and stability, especially in the rivers of Jombang Regency. This research uses descriptive qualitative method with Government Role Theory by Sondang P. Siagian which divides 5 role namely; role as stabilizer, role as innovator, role as modernizer, role as pioneer and role as self-implementer. The result of the study found that the Jombang Regency Environmental Agency has performed is role quite well in controlling river pollution through its role as a stabilizer, role as innovator, role as modernizer, role as pioneer and role as self-implementer. However, there are still some shortcomings in maintaining socio-cultural stability in the form of community complaints regarding waste disposal by the Jombang Baru Sugar Factory which disturbs the comfort of the surrounding environment. Then, there are shortcomings in the applications of phytoremediation innovation in the form of inability to degrade waste in the tofu industry in the Rejoagung 2 river and there is failure of IPAL innovation due to lack of knowledge to operation of IPAL.